Low doses of malathion impair ovarian, uterine, and follicular integrity by altering oxidative profile and gene expression of rats exposed during the peripubertal period - Erthal-Michelato, Rafaela Pires; Frigoli, Giovanna Fachetti; de Aquino, Ariana Musa [UNESP]; Punhagui-Umbelino, Ana Paula Franco; Scarano, Wellerson Rodrigo [UNESP]; Fernandes, Glaura Scantamburlo Alves (Springer Nature, 2024)
Malathion serves as a pivotal pesticide in agriculture and the management of the Aedes aegypti mosquito. Despite its widespread use, there is a notable absence of studies elucidating the mechanisms through which malathion may affect the female reproductive system. Consequently, the objective of this investigation was to assess whether exposing juvenile female rats to low doses of malathion during the juvenile and peripubertal periods could compromise pubertal onset, estradiol levels, and the integrity of the ovaries and uterus while also examining the underlying mechanisms of damage. To achieve this, thirty juvenile female rats were subjected to either a vehicle or malathion (10 mg/kg or 50 mg/kg) between postnatal days 22 and 60, with subsequent verification of pubertal onset. Upon completion of the exposure period, blood samples were collected for estradiol assessment. The ovaries and uterus were then examined to evaluate histological integrity, oxidative stress, and the expression of genes associated with cell proliferation, antiapoptotic responses, and endocrine pathways. Although estradiol levels and pubertal onset remained unaffected, exposure to malathion compromised the integrity and morphometry of the ovaries and uterus. This was evidenced by altered oxidative profiles and changes in the expression of genes regulating the cell cycle, anti-apoptotic processes, and endocrine pathways. Our findings underscore the role of malathion in inducing cell proliferation, promoting cell survival, and causing oxidative damage to the female reproductive system in rats exposed during peripubertal periods.
Keywords: ER upregulation; Female reproductive system; FOXO upregulation; Organophosphate pesticide; Oxidative stress; Postnatal development